Kerukunan Umat Beragama di Kampung Moderasi Beragama Oeleta – Kota Kupang, Nusa Tenggara Timur - Tokan, Gaspar (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This policy paper explains that the socialization of religious moderation villages in Oeleta, Kupang City has not yet functioned optimally, so it still requires additional regulations from the regional government in the form of Governor's Regulations (Pergub) or Mayor's Regulations which focus on regulating the development of religious moderation villages. The purpose of writing this policy paper is to find out the ideal socialization regarding the importance of religious moderation villages and law enforcement regulations related to tolerance in the religious moderation village area in Oeleta. The writing method used is qualitative with a descriptive approach to the results of data findings in the field through observation, interviews, and documentation. The results show that the pilot religious moderation village launched by the Ministry of Religious Affairs in Oeleta does not yet have regulations (Regional Regulations) that form a legal basis, either in the form of NTT Provincial Governor Regulations or Kupang Mayor Regulations. Thus, the author recommends that the Regional Office of the Ministry of Religious Affairs of East Nusa Tenggara Province and the Government of East Nusa Tenggara Province, especially the Governor, make policies to maintain harmony and tolerance between religious communities in NTT, especially in the City of Kupang by strengthening regulations aimed at providing a legal basis for efforts made. carried out to increase religious moderation and tolerance; creating a conducive environment for the development of religious moderation and tolerance; and preventing violations of the principles of religious moderation and tolerance.